Influence of the pairs in the expression of bullying in high school students in Arequipa - Filiberto Bellido; Renzo Rivera; Julio C. Salas; Verónica Bellido; Norma Peña; Guillermo Villasante; Yesenia Casapía (Interacciones, 2016)
The aim of this study was to determine the degree of influence of the proximity of high school students with peers who break rules on the role assumed these students within the bullying (bully, victim or viewer) in the metropolitan area of ​​the city Arequipa, considering sex and level of education. We evaluated 3979 high school students from state, private and parastatal schools in 19 districts in the province of Arequipa, aged between 11 and 19 years. A descriptive and binary logistic regression and multiple linear analysis was performed to model the association between variables. The results show a greater tendency of men to aggressive behavior and assume roles of "bully". The influence of offenders pairs of rules favors greater practical role of aggressor or victim. As for the frequency of bullying, there is a high prevalence of perpetrators and victims among respondents, nearly half of the sample, while the other part is for the spectators whether these enhancers bullying or prosocial.